Prowling through palm: Exploring spatial patterns of male Sunda leopard cats across two oil palm plantations in Kinabatangan, Sabah - Amanda Wilson; Henry Bernard; Macarena Gonzalez-Abarzúa; Sergio Guerrero-Sanchez; Liesbeth Frias; Miriam Kunde; Benoît Goossens (Wiley, 2025)
Industrial oil palm plantations are a major driver of biodiversity loss in South- east Asia, alongside other industries like pulpwood production and logging activities that expedite habitat fragmentation and destruction. Despite this, some native species are highly adaptable within these environments. Our study investigates the space use of leopard cats (Prionailurus Javanese's) within oil palm plantations adjacent to degraded forest fragments in the Kinabatangan floodplain, Sabah, Malaysian Borneo. From March to September 2020, we cap- trued and collared four male cats with Global Positioning System collars, accu- mulating a total of 13,206 successful locational points. We estimated the home ranges using the Minimum Convex Polygon (MCP) and Adaptive Localized Convex Hull (a-Loco) methods. The average home ranges were 8.60 km 2 ± 1.98 (±SD) [95% MCP] and 5.39 km2 ± 1.23 [95% a-Loco], with corresponding core areas of 2.55 km 2 ± 0.99 (±SD) [50% MCP] and 1.05 km 2 ± 0.30 [50% a-Loco]. The home ranges of male leopard cats over- lapped (7% to 28%), while core areas remained exclusive. Despite significant variations in individual habitat use, these cats were detected more frequently in oil palm habitat, occupying 80.89% of their home range and 78.38% of core area. These cats relied more on buffer zones contiguous to plantation area rather than adjacent secondary forests, highlighting the importance of preserve- Ing High Conservation Value (HCV) forests.